2004
DOI: 10.1002/adma.200400758
|View full text |Cite
|
Sign up to set email alerts
|

Patterned Orientations of Liquid Crystals on Affinity Microcontact Printed Proteins

Abstract: ELX-02C ellipsometer with a 632.8 nm laser at a 70 angle of incidence. AFM images were obtained with a Digital Instruments Nanoscope III in tapping mode. Optical images were obtained with a Nikon Eclipse ME600L microscope using the DN100 image capture system.Fabrication of Polymer Objects: Gold substrates were patterned by microcontact printing of thiol initiator using a PDMS stamp and ªbackfillingº by immersion in a 5 mM ethanolic solution of undecanethiol for 30 s. Polymer brushes of poly(glycidyl methacryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…This point is illustrated in this section by describing LC ordering on surfaces presenting oligopeptides. Here we also note that, although LCs can report proteins on surfaces, the complexity of proteins has hindered identification of the intermolecular forces acting between the proteins and LCs [42, 50]. The simpler structure of oligopeptides as compared to full proteins, as well as the ability to make systematic modifications to oligopeptide structure and stereochemistry has led to fundamental insight into the intermolecular interactions underlying the ordering of LCs at biomolecular interfaces [42].…”
Section: Lc-based Sensing Of Biomolecules Displayed On Surfacesmentioning
confidence: 99%
“…This point is illustrated in this section by describing LC ordering on surfaces presenting oligopeptides. Here we also note that, although LCs can report proteins on surfaces, the complexity of proteins has hindered identification of the intermolecular forces acting between the proteins and LCs [42, 50]. The simpler structure of oligopeptides as compared to full proteins, as well as the ability to make systematic modifications to oligopeptide structure and stereochemistry has led to fundamental insight into the intermolecular interactions underlying the ordering of LCs at biomolecular interfaces [42].…”
Section: Lc-based Sensing Of Biomolecules Displayed On Surfacesmentioning
confidence: 99%
“…11 Moreover, the long-range orientational order and large optical anisotropy of the LC can transform various surface events into amplified optical signals that can be easily observed without expensive detection systems. 7,9,10 In this letter, we propose a novel method for detecting hybridization results in a DNA chip using an anchoring transition of LC alignment. To investigate the effects of structural changes of DNA on the LC alignment, we used a functional substrate on which single-stranded oligonucleotide DNA ͑ssDNA͒ was immobilized to the surface.…”
mentioning
confidence: 99%
“…On areas of the surface presenting microcontact printed proteins (squares), the orientation of the pure 5CB was parallel to the surface (planar) with a preferred azimuthal orientation. We have previously reported that the azimuthal orientation of liquid crystals on microcontact printed proteins closely follows the azimuthal direction of contact between the stamp and the surface [16]. On the regions of the ammonium-terminated monolayer that did not support anti-biotin IgG (between squares), the 5CB became bright when the sample was rotated by an angle of 45 • .…”
Section: Influence Of Photochemical Degradation On Microcontact Printingmentioning
confidence: 94%
“…Chemically functionalized surfaces provide access to a wide range of interfacial properties through the introduction of interactions that involve hydrogen bonding [1][2][3][4][5], electrical double of this phenomenon for the creation of chemical and biological sensors based on liquid crystals [16,[25][26][27][28][29]. Although it is well established that the ordering of liquid crystals is sensitive to the molecular-level structure of interfaces [30], the types of chemically functionalized surfaces and liquid crystals that are relevant to the creation of chemical and biological sensors differ from those typically studied in the past in the context of creating electro-optical technologies such as liquid crystal displays (e.g., surfaces prepared from polyimides).…”
Section: Introductionmentioning
confidence: 99%